Outing class in the process of internationalisation. Issue 1 (2nd January 2021) - Muñoz-García, Ana Luisa
ABSTRACT: This article focuses on the ways in which international students from Chile narrate their experiences in the US, and the extent to which mobility across national borders reshapes social class understandings and privilege. To complete this study, I conducted 13 in-depth interviews and a focus group with five Chilean graduate international students who enrolled in an elite research university in the Northeastern region of the United States. The data raised questions about how social class is negotiated in both education and space, challenging how we understand the relationship between social class and education in a global context. I argue that through a process of international mobility, upper-class students from Chile lose class privilege, which in turn influences them to denaturalise their class constructions. Based on discussion of social class within the sociology of education and insights from whiteness studies, the results of my study enable a dialogue about how mobility affects individuals within an international context. I conclude that while international mobility demands students to rethink their class constructions, the affective disruption of silence and guilt emerge as two strategies to justify and perpetuate social class privilege.